Applied Islamic Values in the Practice of Religious Moderation For Students of Islamic Boarding School Students in Lasem District - Moh Sholihuddin; Nafiul Lubab; Jajang Abdul Hamid (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2026)
Abstrak Penelitian ini membahas tentang praktik moderasi beragama yang dilakukan santri Pondok Pesantren di Kecamatan Lasem, kemudian menggali bagaimana penerapan nilai-nilai Islam terapan dalam praktik moderasi beragama tersebut serta faktor-faktor apa saja yang mendukung dan menghambat penerapan nilai-nilai Islam terapan dalam praktik moderasi beragama. Peneliti menggunakan jenis penelitian kualitatif deskriptif, setting penelitian di pondok pesantren Kecamatan Lasem, dengan subjek penelitian santri, kyai, dan tokoh masyarakat Tionghoa dan objek penelitian adalah praktik moderasi beragama santri dan nilai-nilai Islam Terapan. Metode pengumpulan data menggunakan wawancara, observasi, dokumentasi. Analisis data menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini adalah praktik moderasi beragama santri dan analisis nilai Islam terapan adalah: (a) komitmen kebangsaan berupa praktik upacara bendera 17 Agustus sesuai nilai hubbul wathan (cinta tanah air), ruhul wathaniyyah (semangat patriotisme), ukhuwah (persatuan), (b) toleransi berupa kegiatan buka bersama bernilai Islam silaturrahmi, tasamuh (toleransi), hishshotussa’adah (berbagi kebahagian), ruhul amal al-jamaiy (semangat kebersamaan), quwwatul insijam (kekuatan kerukunan). (c) anti-kekerasan berupa kegiatan tegur sapa selaras dengan nilai nilai al-mahabbah (kasih sayang), as-salam wal amnu (kedamaian dan keamanan). (d) Akseptabilitas terhadap budaya lokal berupa praktik ro’an dan haul pesantren. Ro’an bernilai ta’awun (kerjasama), an-nadhafah (kebersihan) dan haul pesantren sesuai nilai ta’awun (kerjasama), al-mas’uliyah al-musytarikah (tanggungjawab bersama). Adapun daya dukung praktik moderasi beragama santri adalah pesantren di Lasem lebih inklusif dan ada waktu tertentu santri berinteraksi dengan masyarakat. Sedangkan daya hambatannya adalah masifnya pemberitaan di media sosial tentang radikalisme, adanya santri yang tidak menerima tradisi masyarakat, dan faktor keragaman pemahaman santri. Kata Kunci: Nilai-Nilai Islam Terapan, Praktik Moderasi Beragama, Santri. Abstract This study discusses the practice of religious moderation carried out by students of Islamic boarding schools in Lasem District, then explores how the application of applied Islamic values in the practice of religious moderation is carried out, as well as the factors that support and hinder the application of applied Islamic values in the practice of religious moderation. The researcher uses a descriptive qualitative research type, with the research setting in the Lasem District Islamic boarding schools, the research subjects being the students, clerics, and Chinese community leaders, and the research object being the religious moderation practices of the students and applied Islamic values. Data collection methods include interviews, observations, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. The results of this study are the students' religious moderation practices and the analysis of applied Islamic values are: (a) National commitment in the form of flag ceremony practice on August 17 in accordance with the values of hubbul wathan (love of homeland), ruhul wathaniyyah (patriotic spirit), ukhuwah (unity). (b) Tolerance in the form of breaking the fast together activities that reflect Islamic values of silaturrahmi (friendship), tasamuh (tolerance), hishshotussa’adah (sharing happiness), ruhul amal al-jamaiy (spirit of togetherness), quwwatul insijam (strength of harmony). (c) Anti-violence in the form of greeting activities in line with the values of al-mahabbah (love), as-salam wal amnu (peace and security). (d) Acceptability of local culture in the form of ro’an and pesantren haul practices. Ro’an embodies the values of ta’awun (cooperation), an-nadhafah (cleanliness), and the pesantren haul aligns with the values of ta’awun (cooperation) and al-mas’uliyah al-musytarikah (shared responsibility). The supporting factor of santri religious moderation practices is that pesantrens in Lasem are more inclusive and there are specific times when santri can interact with the community. Meanwhile, the inhibiting factors are the widespread reporting on social media about radicalism, santri who do not accept community traditions, and the diversity of santri understanding. Keywords: Applied Islamic Values, Religious Moderation Practices, Santri.